The roles of the F move and its effect on classroom interaction - Purwandari, Junita Duwi (Universitas Negeri Yogyakarta, 2021)
This study investigated the role of the teachers' F move in the English as a foreign language (EFL) classrooms and how it affected teacher-student interaction in the classroom. The F move, also known as feedback, is considered an important part of the classroom interaction as it serves two primary roles: evaluative and discoursal. This study used secondary data of classroom interaction during English lesson in two senior high schools in Indonesia. The data were then analysed using the Conversation Analysis (CA) approach. The findings of the current study showed that the teachers used the F move mostly served its evaluative role and there was no evidence of the F move serving its discoursal role. This study suggested the need for teachers to re-evaluate the current teaching practice, especially the way they provided feedback or used the F move as a response to students' answers.